Analisis Daya Dukung Pondasi Dalam Pada Tanah Granural Overpass STA 13+250 Jalan Tol Tebing – Siantar - Rudianto Surbakti; Tika Ermita Wulandari (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Every building that is built requires a foundation to transmit loads to the surrounding land, therefore the foundation must be designed properly so that the load transferred by the foundation to the ground is not greater than the soil's capacity Deep foundations built on granular soils have different calculation methods compared to ordinary soils. There are several methods that can support the resistance carrying capacity in granular soils. In this study, Mayerhoff and Briaud et al. method used. which will be verified by PDA test results. In this study the efficiency value of the pile group was also calculated using the Los Angeles Group – Action Formula and Conversion – Labarre methods. The purpose of this research is to find out from several analytical methods that are often used, which method is the most effective in use in the field. From the results of the analysis it is known that the carrying capacity with the Mayerhoff - Labarre conversion method is 392,984, the difference is 2,984 tons or 0.77% from the PDA test results of 390 tons, Mayerhoff - Los Angles Action is 296,129 tons, the difference is -24.07%, the conversion of Briaud et Al - Labarre of 294.674 tons with a difference of -24.44% and the conversion of Briaud et Al - Los Angles Action of 222.049 tons with a difference of -43.06%. So it can be concluded that the Mayerhoff method with pile group efficiency using the Labarre conversion method is closer to the results of field observations (PDA test), which is equal to 0.77%.